(untitled) (Texas Journal of Philology, Culture and History, 2023)
The article analyzes the commentaries on Abu Hafs Umar an-Nasafi’s work "Aqoid un-Nasafi" and the controversy that the work "Nazmi Aqoid" belongs to Alisher Navoi.